2014
DOI: 10.1002/jhm.2188
|View full text |Cite
|
Sign up to set email alerts
|

Caring for patients in a hospitalist‐run clinical decision unit is associated with decreased length of stay without increasing revisit rates

Abstract: BACKGROUND Observation medicine is a growing field with increasing involvement by hospitalists. Little has been written regarding clinical outcomes in hospitalist‐run clinical decision units (CDUs). OBJECTIVE To determine the impact of a hospitalist‐run geographic CDU on length of stay (LOS) for observation patients. Secondary objectives included examining the impact on 30‐day emergency department (ED) or hospital revisit rates. DESIGN Retrospective cohort study with pre‐ and post‐implementation analysis. SETT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Multidisciplinary rounds, e.g., on a vascular surgery service, were found to decrease LOS but not lead to any significant effect on readmissions [10]. We have previously shown that decreasing observation LOS in a hospitalist-run clinical decision unit is not associated with an increased rate of emergency department visits or readmissions [11].…”
Section: Introductionmentioning
confidence: 84%
“…Multidisciplinary rounds, e.g., on a vascular surgery service, were found to decrease LOS but not lead to any significant effect on readmissions [10]. We have previously shown that decreasing observation LOS in a hospitalist-run clinical decision unit is not associated with an increased rate of emergency department visits or readmissions [11].…”
Section: Introductionmentioning
confidence: 84%
“…7 These units are normally run by physicians/ surgeons and facilitate the rapid assessment and intensive management of patients by their relevant specialties. [7][8][9][10][11][12][13][14][15][16][17][18][19] The CDU model of care was commonly reported to be a cost-effective alternative to the clinical management of patients who may otherwise be hospitalised. 8 A preliminary MEDLINE literature search identified 13 studies assessing the impact of the introduction of these types of units on key performance indicators (KPIs) such as access block, hospital length of stay, re-presentation rate or time to tests or physician review.…”
Section: Introductionmentioning
confidence: 99%
“…8 A preliminary MEDLINE literature search identified 13 studies assessing the impact of the introduction of these types of units on key performance indicators (KPIs) such as access block, hospital length of stay, re-presentation rate or time to tests or physician review. [7][8][9][10][11][12][13][14][15][16][17][18][19] The CDU model of care was commonly reported to be a cost-effective alternative to the clinical management of patients who may otherwise be hospitalised. 8 The Hervey Bay CDU model Hervey Bay hospital is a public facility with 119 inpatient beds and an ED that sees approximately 35 000 patients per annum.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 OUs decrease length of stay, readmission rate, and cost while improving outcomes and patient satisfaction. [5][6][7][8][9][10][11] OUs are useful for providing care to elderly patients who do not require prolonged admissions. They provide the opportunity to further evaluate a patients' functional status and home care needs, perform medication reconciliation, and provide multidisciplinary care.…”
mentioning
confidence: 99%
“…3,4 OUs decrease length of stay, readmission rate, and cost while improving outcomes and patient satisfaction. 5-11…”
mentioning
confidence: 99%